Political parties and network formation - Topi Miettinen; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2006)
We argue that anticorruption laws may provide an efficiency rationale for why political parties should meddle in the distribution of political nominations and government contracts. Anticorruption laws forbid trade in spoils that politicians distribute. However, citizens may pay for gaining access to politicians and, thereby, to become potential candidates for nominations. Such rent-seeking results in excessive network formation. Political parties may reduce wasteful network formation, thanks to their ability to enter into exclusive membership contracts. This holds even though anticorruption laws also bind political parties.
Keywords: L14; D85; D72; 330; political parties; two-sided platforms; rent-seeking; network formation; Patronage; Rent Seeking; Soziales Netzwerk; Politische Partei; Klubtheorie; Theorie